Kemajuan Teknologi dan Kecepatan Perputaran Uang: Studi Kasus Indonesia - Mutia Huljannah; Doni Satria (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2021)
Technological developments and financial innovations, especially in the payment system, have encouraged banks around the world to carry out a number of innovations that have resulted in a new paperless based financial system. The finding that the payment system innovation affects the circulation of money and the stability of the monetary condition of a country, makes this risk possible in Indonesia. By using the error correction model, this study can provide information on the short run dynamic relationship and the impact of payment system innovation represented by non cash payment instruments such as credit cards, debit cards, e-money and payment transaction settlement processes (national clearing system and real time gross settlement) on the velocity of money in Indonesia in the period 2016M1 to 2020M6. The results of the research findings state that the impact generated by the rapid velocity of payment system innovation on the velocity of money circulation is not temporary, this is evidenced by the effect of payment system innovation on the velocity of money circulation which continues over a long period of time.